UPRmt-regulated mitokines: novel strategies for myocardial injury repair - Gao, Weinan; Liu, Jia; Zhang, Wenda; Liu, Bin; Shen, Luyan (Frontiers in Cell and Developmental Biology, 2025)
Cardiac mitochondria generate ATP, via oxidative phosphorylation (OXPHOS) to sustain continuous and forceful myocardial contraction, thereby meeting systemic metabolic demands. Mitochondrial biogenesis and energy metabolism depend on proteostasis, which can be disrupted by stressors such as hypoxia, leading to impaired cardiac function. As a result, the study of mitochondrial energy metabolism and proteostasis under stress has become a key focus in cardiovascular research. The mitochondrial unfolded protein response (UPRmt) plays a “double-edged sword” role—either protective or detrimental—depending on the type, intensity, and duration of the stressor. This has sparked interest in strategies aimed at enhancing its adaptive signaling while inhibiting maladaptive pathways. Acting as mediators of intercellular communication, mitokines may transmit local mitochondrial stress signals to mitochondria in distant cells and tissues. This review analyzes and summarizes the role of UPRmt in regulating mitochondrial factors and explores the mechanisms through which fibroblast growth factor 21 (FGF21), secreted by the liver and skeletal muscle, influences protein homeostasis in cardiac myocytes. These insights aim to offer new avenues for the development of targeted UPRmt therapies and rehabilitation strategies for heart diseases.